Harmonious governance frameworks for water reuse: guidelines for planners, investors, project designers and operators - International Water Management Institute (International Water Management Institute, 2023)
Effective governance is central to successful water reuse in the Middle East and North Africa (MENA), where water scarcity is intensifying due to population growth and agricultural pressure. This IWMI brief under the ReWater MENA project outlines a thirteen-step approach for designing inclusive, functional governance frameworks that accommodate the diverse range of formal and informal stakeholders in water reuse from ministries and farmers to NGOs and private operators. It emphasizes consensus-building through multi-stakeholder platforms, mapping institutional gaps, aligning roles and responsibilities, and ensuring data transparency. Real-world cases from Jordan and Lebanon illustrate how local dialogue, standards development, and coordination can improve water reuse acceptability and policy coherence. The brief stresses flexibility in institutional roles, capacity-building for public administrations, and nurturing trust among actors. By recognizing local expertise while avoiding governance ambiguity, IWMI presents a blueprint for collaborative, adaptive water reuse management that is vital for sustainable development across the region.